THE RELATIONSHIP BETWEEN WORK ENVIRONMENT, INTERPERSONAL RELATIONSHIP AND EMPLOYEE JOB SATISFACTION IN PONDOK PESANTREN DAARUL ‘ULUM MUHAMMADIYAH SEWUGALUR KULON PROGO - Edi Kurniawan; Ema Nurmaya; Abdul Choliq Hidayat (Universitas Sarjanawiyata Tamansiswa, 2022)
This study investigates the effect of the Work Environment and Interpersonal Relationships on Job Satisfaction. An eighty respondents of the employees of the Daarul `Ulum Muhammadiyah Islamic Boarding School Sewugalur Kulon Progo are solicited to participate in this study. Data collection using questionnaires and data analysis with multiple linear regression analysis using SPSS 25 program. The results shows that the Work Environment has no effect on Job Satisfaction. Interpersonal Relationhip has a positive effect on Job Satisfaction, and both of Work Environment and Interpersonal relation have a simultaneous effect on Job Satisfaction. Several contributions are sugested for managerial and future research.